1988
DOI: 10.1007/bf00117291
|View full text |Cite
|
Sign up to set email alerts
|

Use of variance techniques to measure dry air-surface exchange rates

Abstract: The variances of fluctuations of scalar quantities can be measured and interpreted to yield indirect estimates of their vertical fluxes in the atmospheric surface layer. Strong correlations among scalar fluctuations indicate a similarity of transfer mechanisms, which is utilized in some of the variance techniques. The ratios of the standard deviations of two scalar quantities, for example, can be used to estimate the flux of one if the flux of the other is measur+-d, without knowledge of atmospheric stability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 28 publications
1
52
1
Order By: Relevance
“…[Wesley, 1988], the value of C•(1.3) found in this study is large. However, as mentioned before, the measurements in the pine forest were performed near the canopy-atmosphere interface.…”
Section: Discussioncontrasting
confidence: 54%
“…[Wesley, 1988], the value of C•(1.3) found in this study is large. However, as mentioned before, the measurements in the pine forest were performed near the canopy-atmosphere interface.…”
Section: Discussioncontrasting
confidence: 54%
“…McNaughton and Brunet (2002) even argued that interactions between such inactive and active eddy motions responsible for momentum transfer are also possible within the ASL and proposed a simplified mechanism for its onset. Likewise, a large number of studies (Wesley 1988;Weaver 1990;Padro 1993;Andreas et al 1998) have shown how source-sink in-homogeneity at the ground induces departure between measured FV similarity functions and predictions from MOST.…”
Section: Discussionmentioning
confidence: 99%
“…The variance methods are based on 22 flux-variance relationships derived on the basis of similarity arguments and established through the 23 determination of the constant parameters in the derived relationship. Such relations have been established 24 and verified extensively through experiments in the surface layer and it now appears possible to derive 25 surface fluxes with sufficient accuracy (e.g., Wesely, 1988;Katul et al, 1996). In contrast, for the CBL, the 26 relevant flux-variance relationships are still not fully understood and far from established.…”
Section: Introduction 1mentioning
confidence: 92%